TNFα blockers and infectious risk in rheumatoid arthritis - S. Todesco; P. Sfriso; A. Montante; L. Bernardi; F. Ometto; C. Botsios; B. Raffeiner; L. Punzi (PAGEPress Publications, 2011)
Patients suffering from rheumatoid arthritis have increased risk of infections when compared with general population. The risk depends directly from disease activity and severity. Furthermore, risk increases with aging, immunosuppressive agents and comorbidities such as diabetes, pulmonary and cardiac diseases. In particular corticosteroids, even at low doses, are a major risk factor. Due to disease related risk it is difficult to separate the risk deriving from the use of TNF alpha blockers. Data from clinical trials, meta-analysis and national registers are somewhat contradictory. In patients with rheumatoid arthritis on routine follow-up, treatment with TNF alpha blockers seems to carry an increased risk of infections compared to traditional DMARDs but not associated with increased risk of overall serious infection. Physicians should carefully monitor for signs of infection when using TNF alpha blockers, particularly shortly after treatment initiation.